Determination of Loading Scenarios on Buildings Due to Column Damage. (November 2017) - Colomer Segura, Carles; Hamra, Lotfi; D'Antimo, Marina; Demonceau, Jean-François; Feldmann, Markus
Abstract: The majority of imaginable (and relevant) accidental scenarios on building structures are initiated at the ground level by a column suffering damage, mainly due to a localized explosion or a vehicle impact. The transmitted vertical forces from the column to the structure are decisive in understanding the response of the building and are the subject of analysis of this paper. The classic definition of a column loss scenario is extended here by means of a simplified analytical approach to characterize the axial forces appearing in the column during the damage process. A simple closed-form solution is proposed to define the loading scenario on the structure and compared to the classic rectangular (un)loading approach. In certain cases, the proposed analysis shows a more unfavorable loading situation for the structure, which needs to be accounted for during design.